Detection of divergent Orthohantavirus tulaense provides insight into wide host range and viral evolutionary patterns - Mert Erdin; Teemu Smura; Kursat Kenan Kalkan; Ortac Cetintas; Muhsin Cogal; Sercan Irmak; Ferhat Matur; Ceylan Polat; Tarja Sironen; Mustafa Sozen; Ibrahim Mehmet Ali Oktem (npj Viruses)
Abstract Orthohantavirus tulaense (TULV) is a member of the orthohantavirus genus and distributed in Europe and Asia. To shed light on TULV epidemiology and evolution, we trapped wild rodents from eastern Turkiye and found 15 TULV positive rodents. Sequencing and phylogenetic analyses confirmed the presence of diverse TULV strains. Global phylogenetic characterization suggested 5 distinct TULV lineages. Global phylogeographic reconstruction estimated different rooting times for each three segments, a potential ancestor location in Eastern Black Sea region, and strongly supported phylogeographic structure with 11 clusters. Dispersal velocity of TULV was estimated to be much faster than some other orthohantaviruses. Eastern Black Sea seemed to have lineages evolving faster and genetically closer to proto-Tula virus. Host switching estimates suggested potential switching events from Microtus arvalis to M. obscurus to M. irani with host-dependent sub-clustering within geographic clusters and suggested substantial evidence for no clear virus jumps from M. arvalis to M. irani.